Initial experience with hemostatic fibrin glue as adjuvant during drainless parotidectomy - Khalid AL-Qahtani (Elsevier, 2011)
Objectives: To evaluate the use of Hemostatic Fibrin Glue in parotidectomy without the use of surgical drains. Study design: Prospective cohort study of 10 patients undergoing parotidectomy. Surgery as a one day admission without the use of surgical drains was planned. The complication and duration of the hospital stay were obtained. Methods: Parotidectomy was undertaken by one surgeon. Prior to wound closure, the skin flap and wound bed were approximated using Tisseel tissue sealant. Data regarding the incidence of any complication and the duration of the hospital stay were obtained. Patients were followed to assess surgical outcome and document any complications. The mean follow-up period was 8 months (range 4-12 months). Results: There were no major surgical complications. Two patients had facial nerve weakness due to adherence of the tumour in the facial nerve, in there was which complete recovery after few months. All patients were discharged the next day. None of the patients felt that the discharge had been premature. Conclusions: Parotidectomy can be undertaken safely without the need for surgical drains, therefore, allowing the patients to leave the hospital on the first postoperative day. Keywords: Tisseel, Fibrin glue, Drainless parotidectomy, Seroma, Hematoma